Evaluation of a commercial kit for the routine detection of Clostridium difficile cytotoxin by tissue culture. - Wu, T C (1986)
The Toxi-titer microtiter plate system (Bartels Immunodiagnostic Supplies, Inc., Bellevue, Wash.) is a simplified procedure for detecting the cytotoxin produced by Clostridium difficile in stool filtrates. In a parallel study of 74 stool specimens, results from the Toxin-titer system compared favorably with those from the conventional system. Our experience with the Toxin-titer system in testing 540 stool specimens was, in general, satisfactory, although a few problems with toxin control did occur. The method requires no specialized experience in tissue culture techniques and can therefore be adopted for routine use in clinical laboratories.